Environmental Impact on Differential Composition of Gut Microbiota in Indoor Chickens in Commercial Production and Outdoor, Backyard Chickens - Seidlerova, Zuzana; Kubasova, Tereza; Faldynova, Marcela; Crhanova, Magdalena; Karasova, Daniela; Babak, Vladimir; Rychlik, Ivan (Microorganisms, 2020)
In this study, we compared the caecal microbiota composition of egg-laying hens from commercial production that are kept indoors throughout their whole life with microbiota of hens kept outdoors. The microbiota of outdoor hens consisted of lower numbers of bacterial species than the microbiota of indoor hens. At the phylum level, microbiota of outdoor hens was enriched for Bacteroidetes (62.41 ± 4.47% of total microbiota in outdoor hens and 52.01 ± 6.27% in indoor hens) and Proteobacteria (9.33 ± 4.99% in outdoor and 5.47 ± 2.24% in indoor hens). On the other hand, Firmicutes were more abundant in the microbiota of indoor hens (33.28 ± 5.11% in indoor and 20.66 ± 4.41% in outdoor hens). Horizontally transferrable antibiotic resistance genes tetO, tet(32), tet(44), and tetW were also less abundant in the microbiota of outdoor hens than indoor hens. A comparison of the microbiota composition at the genus and species levels pointed toward isolates specifically adapted to the two extreme environments. However, genera and species recorded as being similarly abundant in the microbiota of indoor and outdoor hens are equally as noteworthy because these represent microbiota members that are highly adapted to chickens, irrespective of their genetics, feed composition, and living environment.
Keywords: caecum; chicken microbiota; backyard chicken; microbiome; environment